Steinbeck Galleries in Palms Springs, California - unknown:::Creator::::::::::::
A color photo of the Steinbeck Galleries in Plam Springs, California. Reference to such a gallery at this location found at http://palmspringslife.com/media/Palm-Springs-Life/December-1967/. See number 1 251. Color photo.